2008
DOI: 10.1111/j.1444-2906.2008.01656.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of intestinal bacteria of freshwater salmonSalmo salarand sea troutSalmo trutta truttaand diet

Abstract: The microbial diversity of culturable intestinal microflora of wild freshwater salmonid fishes salmon Salmo salar and sea trout Salmo trutta trutta juveniles (0+ years old) from the same environmental conditions were investigated by means of molecular identification techniques and analysis of diet. Significant differences in the intestinal microbial diversity were observed in different fish species. The predominant group in the intestinal tract of the salmon comprised representatives of the Enterobacteriaceae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 36 publications
2
28
0
2
Order By: Relevance
“…So the association of several bacteria in the intestinal tract of milkfish have the ability to defend itself against disease. This results were similar with several other studies that has been published [27,28,29,30]. The criteria of bacterial probiotics candidate should has the ability to inhibit pathogenic bacteria and able to compete with pathogenic bacteria in the intestinal tract.…”
Section: Bacterial Sensitivity Testsupporting
confidence: 94%
“…So the association of several bacteria in the intestinal tract of milkfish have the ability to defend itself against disease. This results were similar with several other studies that has been published [27,28,29,30]. The criteria of bacterial probiotics candidate should has the ability to inhibit pathogenic bacteria and able to compete with pathogenic bacteria in the intestinal tract.…”
Section: Bacterial Sensitivity Testsupporting
confidence: 94%
“…; Bacanu and Oprea ), but results from studies that compared several fish species collected from the same area showed a marked specificity between fish species and microbiota (Skrodenyte‐Arbaciauskiene et al . ; Smriga et al . ; Larsen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Only about 1% of all gut bacteria in fish can be cultured, including Enterobacteriaceae , Pseudomonas spp., Staphylococcus spp., Acinetobacter spp., Aeromonas spp., Vibrio spp. and Bacillus spp., which severely limited early assessments of fish intestinal microbiota (Merrifield et al, 2009), with a limited number of species cultivated from zebrafish (Cantas et al, 2012) and trout (Skrodenyté-Arbačiauskiené et al, 2008). In Atlantic salmon limited species richness was found by TTGE (Navarrete et al, 2009a) and DGGE (Reveco et al, 2014).…”
Section: Introductionmentioning
confidence: 99%